Color atlas of anatomy : a photographic study of the human body - Rohen, Johannes W. [ (Johannes Wilhelm)]; Lütjen-Drecoll, Elke; Yokochi, Chihiro (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"This Color Atlas of Anatomy features outstanding full- color photographs of actual cadaver dissections, with accompanying schematic drawings and diagnostic images. The photographs depict anatomic structures more realistically than illustrations in traditional atlases and show students exactly what they will see in the dissection lab." "Chapters are organized by region in order of a typical dissection. Each chapter presents structures both in a systemic manner from deep to surface, and in a regional manner." "This edition has additional clinical imaging, including MRIs, CTs, and endoscopic techniques. New graphics include clinically relevant nerve and vessel varieties and antagonistic muscle functions. Many older images have been replaced with new, high-resolution images. Black-and-white dissection photographs have been replaced with color photography." --Book Jacket